FUNDAMENTALISME DAN GERAKAN POLITIK IDENTITAS - Kholid Mawardi (Komunika, 2015)
Abstract Violence is not the monopoly of religious radical groups, but also in other fields. For example sports, especially soccer, has spawned radical movements that also frequent violence in the name of exclusivity group, which known as hooligans supporters groups. Violence which on behalf of ethnic also occurred in Africa, as it did in 1959 and 1994, where clashes between Hutus by Tutsis Tribes that resulted in thousands and even millions of Tutsis were killed. This paper intends to describe the fundamentalism, how its emergence, its characteristics, and the spread of their parts of the world. Fundamentalism is a radical views and attitudes, militant, narrow-minded , excited in excess (ultra - jealous) or have a tendency to achieve goals with violent means, thereby actually radicalism and terrorism intertwined in it.